2019
DOI: 10.3390/cancers11121876
|View full text |Cite
|
Sign up to set email alerts
|

HMGCS2 Mediates Ketone Production and Regulates the Proliferation and Metastasis of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignant tumor worldwide; however, the traditional therapeutic approaches and survival rates are still limited. To improve current therapies, it is necessary to investigate the molecular mechanisms underlying liver cancer and to identify potential therapeutic targets. The aims of this study were to verify the mechanisms and therapeutic potential of the ketogenesis rate-limiting enzyme 3-Hydroxymethylglutaryl-CoA synthase 2 (HMGCS2) in HCC. Immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 56 publications
(76 reference statements)
1
59
0
Order By: Relevance
“…Its inactivation in hepatocellular carcinoma has been veri ed and was positively associated with ketone body production. Importantly, the ketone bodies inhibit tumor cell migration by reversing epithelialmesenchymal transition (EMT) signaling (28). Similarly, we showed that the epithelial markers (CDH1 and EPCAM) were increased in NPC cells after overexpressing ACAT1, while mesenchymal markers (vimentin and SPARC) were decreased.…”
Section: Discussionmentioning
confidence: 69%
“…Its inactivation in hepatocellular carcinoma has been veri ed and was positively associated with ketone body production. Importantly, the ketone bodies inhibit tumor cell migration by reversing epithelialmesenchymal transition (EMT) signaling (28). Similarly, we showed that the epithelial markers (CDH1 and EPCAM) were increased in NPC cells after overexpressing ACAT1, while mesenchymal markers (vimentin and SPARC) were decreased.…”
Section: Discussionmentioning
confidence: 69%
“…Previously, we reported that HMGCS2 protein expression is significantly reduced in liver tissues from HCC patients. Moreover, the expression of HMGCS2 was negatively correlated with the pathological grade and clinical stage [ 29 ]. We found that HMGCS2 controls the proliferation and migration abilities of liver cancer cells by regulating the apoptosis, c-Myc/cyclin D1, and EMT signaling pathways and acts in a ketone-dependent manner [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of HMGCS2 was negatively correlated with the pathological grade and clinical stage [ 29 ]. We found that HMGCS2 controls the proliferation and migration abilities of liver cancer cells by regulating the apoptosis, c-Myc/cyclin D1, and EMT signaling pathways and acts in a ketone-dependent manner [ 29 ]. Thus, using a KD will increase HMGCS2 expression, and thereby, enhance ketone production to inhibit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations